Spectroscopy of diethyl carbonate, a green solvent: An experimental and theoretical study. (September 2018) - Das, Asim Kumar; Rajasekhar, B.N.; Krishnakumar, Sunanda
Highlights: Electronic photoabsorption spectrum (using synchrotron radiation) of diethyl carbonate (DEC) recorded in the 7- to 11-eV region is reported for the first time. Gas-phase infrared spectrum of DEC revisited in the 600- to 3100-cm −1 region to obtain a comprehensive set of assignments for the vibrational modes. Vertical excited state energies and the nature of transitions calculated using the TDDFT methodology. Potential energy curves of the first few excited states studied to predict the photo-dissociation of the molecule. Analysis of the photoabsorption spectra of DEC in the VUV region substantiated with quantum chemical calculations. Abstract: The electronic spectra of diethyl carbonate (DEC) based on photoabsorption spectroscopy using synchrotron radiation are investigated in the 6.8-11.5 eV region. The VUV photo absorption spectrum reported here for the first time comprises broad features in the 7-11 eV region with few weak overriding spectral peaks. The broad peaks could be assigned to valence excitations, while the weak ones correspond to the Rydberg series of ns, np, and nd types, thus converging to the first five ionization potentials. Quantum defect values obtained are consistent with the excitation of an electron from oxygen lone pair. Infrared bands of DEC were revisited in the 600-3100 cm −1 region. The observed infrared bands of DEC could be assigned by DFT calculations. The TDDFT methodology is used to compute the vertical excited state energies, valence/Rydberg nature, and oscillator strengths of the excited electronic states. A good agreement using the CAM-B3LYP level of theory is achieved between the theoretically predicted values and experimental observations. In the ionic limit of DEC, the lengthening of the CO and CO–C2 H5 bond lengths is predicted. The potential energy curves of the first few excited states assisted in additional insights on the nature of the excited states and their role in photo dissociation dynamics. This study gives a first comprehensive report on the analysis of absorption spectra of DEC in the VUV region and the complete spectral assignments in the VUV and IR regions by quantum chemical calculations.